Climate Policy Curves: Linking Policy Choices to Climate Outcomes - Martin C. Hänsel; Michael D. Bauer; Moritz A. Drupp; Gernot Wagner; Glenn D. Rudebusch (Center for Economic Studies and ifo Institute (CESifo), 2022)
The extent of future climate change is a policy choice. Using an integrated climate-economy assessment model, we estimate climate policy curves (CPCs) that link the price of carbon dioxide (CO2) to subsequent global temperatures. The resulting downward sloping CPCs quantify the inverse relationship between carbon prices and future temperatures and illustrate how climate policy choices determine climate outcomes. Our analysis can account for a variety of climate policies – for example, carbon or fuel taxes, emissions trading programs, green subsidies, and energy-efficiency regulations – all of which can be summarized by means of an effective CO2 price. Importantly, we also examine CPC uncertainty, for example, by perturbing the model's equilibrium climate sensitivity to trace out the temperature range associated with a given CO2 price. Finally, based on the latest Intergovernmental Panel on Climate Change (IPCC) integrated-assessment model scenarios, we estimate an implicit CPC, which provides a high-level IPCC summary of the climate policy actions required to achieve global climate targets.
Keywords: Q54; Q58; 330; climate policy; carbon tax; climate-economy models; model comparison